ANALYSIS OF VOCABULARY USAGE IN THE ANIMATED FILM 'TOY STORY I' AS A MEANS OF ENHANCING ENGLISH PROFICIENCY IN CHILDREN - Ridwan Ghozali; Yousef Bani Ahmad; Dedeh Kartini (PROJECT (Professional Journal of English Education), 2024)
This study employs qualitative content analysis to explore the diverse vocabulary usage within the animated film "Toy Story I" and its potential to enhance English proficiency in children. The research focuses on systematically sampling dialogues categorized into figurative, idiomatic, and slang vocabulary types, unveiling the intricate language dynamics embedded in the film. Through this analysis, the study highlights how exposure to various vocabulary types in multimedia entertainment can contribute to a comprehensive language learning experience. By immersing children in figurative expressions, idiomatic nuances, and contemporary slang, the film engages their critical thinking, cultural awareness, and conversational skills. This holistic approach aligns with established vocabulary acquisition theories, fostering vocabulary retention and promoting a deeper understanding of language nuances. Ultimately, the study underscores the significant role of multimedia entertainment, exemplified by "Toy Story I," in innovatively enhancing language learning strategies for educators, parents, and language development specialists seeking effective methods to elevate children's English proficiency.